Saccharomyces boulardii Ameliorates Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice by Regulating NF-κB and Nrf2 Signaling Pathways. (29th July 2021) - Gao, Hui; Li, Yinzheng; Sun, Jie; Xu, Huzi; Wang, Meng; Zuo, Xuezhi; Fu, Qiang; Guo, Yanchao; Chen, Zhenyan; Zhang, Piwei; Li, Xudong; Wang, Niwen; et al.
Abstract : Saccharomyces boulardii ( S. boulardii ) is a probiotic yeast that is widely used to treat gastrointestinal disorders. The present study is aimed to explore the therapeutic effects of S. boulardii on dextran sulfate sodium- (DSS-) induced murine ulcerative colitis (UC) and illustrate the mechanisms of action. C57BL/6 mice were administered S. boulardii (10 5 and 10 7 CFU/ml, p.o. ) for 3 weeks and then given DSS [2.5% (w / v )] for one week. Administration of S. boulardii prevented DSS-induced reduction in body weight, diarrhea, bloody feces, decreased colon length, and loss of histological structure. Moreover, S. boulardii protected the intestinal barrier by increasing the levels of tight junction proteins zona occludens-1 and Occludin and exerted immunomodulatory effects in DSS-induced mice. Furthermore, S. boulardii suppressed the colonic inflammation by reducing the levels of Interleukin-1 β, Interleukin-6, and Tumor necrosis factor alpha and restored myeloperoxidase activity in mice exposed to DSS. S. boulardii also mitigated colonic oxidative damage by increasing the levels of antioxidant enzymes (superoxide dismutase, catalase, and heme oxygenase 1) and glutathione and decreasing malondialdehyde accumulation. Further studies identified that S. boulardii suppressed the nuclear translocation of nuclear factor kappa B (NF- κ B) p65 subunit by decreasing I κ K α / β levels, while promoted the nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) in DSS-exposed mice. Collectively, S. boulardii possessed an appreciable therapeutic effect against the experimental mice model of UC. The protective mechanism of S. boulardii may involve inhibition of NF- κ B-mediated proinflammatory signaling and activation of Nrf2-modulated antioxidant defense in addition to intestinal barrier protective and immunomodulatory effects.